Electromechanical Devices of Adaptive and Control-Tracking Systems - Kerimzade G.S.; Vishal Jain; Farhana Mahjabeen; Munir Ahmad; Dipak P. Patil; Auwal Garba; Vinod Shantaram Mahajan (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2023)
In the presented work, some characteristics of devices of adaptive and control-tracking control systems are considered. The characteristic features of angle sensors, methods of converting analog signals with high accuracy (for example, sine-cosine transformers) occupies a leading position among the development and research of tracking systems. The modern electronic element base opens up new possibilities - the creation of tracking digital angle converters (TDAC) using the principles of digital tracking and adaptive control in them. Stability, efficiency, load form determines the reliability, accuracy, economy, service life of electromechanical automation devices, test equipment, etc. Determining the characteristics, establishing analytical relationships between the initial data and output parameters is one of the stages of the algorithm for solving the problems of designing equipment parameters for monitoring and tracking control systems, which in turn contributes to the development of a mathematical model from a system of equations, the joint solution of which allows you to establish analytical relationships between the initial data and settings.